2022
DOI: 10.47604/ejbsm.1623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operational Strategies on Performance of Commercial Banks in Makueni County, Kenya

Abstract: Purpose: The purpose of this study was to determine the effect of operational strategies on the performance of commercial banks in Makueni County in respect to banking services. The specific objective of this study was to investigate the influence of debt recovery, promotional strategies, employee training, the quality of bank services and products on the performance of commercial banks in Makueni County. Methodology: The study used cross-descriptive research design and data was collected using a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Furthermore, in the industrial sector, most fraud perpetrators are found in banking and financial services (ACFE, 2020a(ACFE, , 2020b. This aligns with Iminza et al (2015), who argues that fraud is more high-handed in banking than in other industries. As data published by the Financial Services Authority (OJK) that there were 57 banks indicated to commit fraud in 2017 and 36 banks in 2018 to the third quarter (Meliana & Hartono, 2019), and cases of financial statement fraud in the banking sector were the second largest (21%) after credit case (56%).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, in the industrial sector, most fraud perpetrators are found in banking and financial services (ACFE, 2020a(ACFE, , 2020b. This aligns with Iminza et al (2015), who argues that fraud is more high-handed in banking than in other industries. As data published by the Financial Services Authority (OJK) that there were 57 banks indicated to commit fraud in 2017 and 36 banks in 2018 to the third quarter (Meliana & Hartono, 2019), and cases of financial statement fraud in the banking sector were the second largest (21%) after credit case (56%).…”
Section: Introductionsupporting
confidence: 86%
“…Empirically, Salhi & Boujelbene (2012) have examined the relationship between internal governance mechanisms and risk-taking in the banking industry, and Ahmad et al (2021) found a significant relationship between business operational risk and fraud. Iminza et al (2015) have found a positive but weak relationship between governance and operational risk of fraud. Meanwhile, Jaffar (2009) has found that the level of fraud risk has a positive moderating effect on the relationship between the external auditor's ability to assess fraud risk and the external auditor's ability to detect the possibility of fraud.…”
Section: Corporate Governance Operational Risk and Financial Statemen...mentioning
confidence: 99%
“…In accordance to Muhammed (2016), the banking industry provides financial advisory, consulting services and transactions services to customers. In Kenya, the commercial banks are responsible for providing transaction services such as withdrawals and deposits, investment options and loan services to the citizens (Barno & Rotich, 2018). Due to globalization and evolving technologies, Kenya's commercial banks have been witnessing declining performance, increased inflation, competition and new prudential regulations (CBK, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The results indicated that there was a positive statistically significant correlation between product differentiation and the performance of the firm. The study conducted by Maina & Kagiri (2016) focused on the effects of product differentiation strategies on organization competitiveness at East African Breweries Limited, Kenya. The findings indicated that there was a statistically significant correlation between product differentiation and organizational performance.…”
Section: Product Differentiation Strategies and Firm Performancementioning
confidence: 99%